Preparation method of sacrificial salt and C composite pre-ionized material

By combining spray drying and calcination, the in-situ carbon-forming sacrificial salt @C composite pre-ionized materials were prepared, which solved the problems of insufficient conductivity and pore residues of existing sacrificial salt materials, and achieved more efficient active metals Ion release and battery performance improvements.

CN119447526AInactive Publication Date: 2025-02-14SHENZHEN JANAENERGY TECH CO LTD +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411585137.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-07
Publication Date
2025-02-14
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The sacrificial salt materials in existing secondary batteries are insufficiently conductive and severe pore residues, resulting in high decomposition potential and insufficient release of active metal ions, which affects battery performance.

Method used

A combination of spray drying and calcination was used to prepare a sacrificial salt @C composite pre-ionized material that was carbon-formed in situ was formed to form a thin and uniform carbon cladding layer, improve conductivity and fill holes.

Benefits of technology

The decomposition voltage of the sacrificial salt is significantly reduced, allowing it to decompose within the electrochemical window of the electrolyte, maximizing the release of active metal ions, and improving the electrochemical and cycling performance of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119447526A_ABST
    Figure CN119447526A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a sacrificial salt (at) C composite pre-ionized material, which comprises the following steps: S1, preparation of an alkali metal salt-organic carbon source mixed solution: adding a water-soluble organic carbon source into an alkali metal salt solution, and uniformly stirring to obtain the alkali metal salt-organic carbon source mixed solution; s2, preparation of a pre-ionized sacrificial salt compound precursor: spraying out the alkali metal salt-organic carbon source mixed solution through spray drying to obtain the precursor; and S3, preparing an in-situ carbon-forming composite pre-ionized sacrificial salt material: roasting the prepared precursor at a high temperature in a protective atmosphere to obtain the in-situ carbon-forming composite pre-ionized sacrificial salt material. The preparation method of the sacrificial salt and C composite pre-ionized material has the characteristics of low material production cost, good mixing uniformity, excellent electrochemical performance and good electrolyte wettability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of secondary batteries, and in particular to a method for preparing a sacrificial salt@C composite pre-ionized material. Background Art

[0002] Sacrificial salts are a simple and effective means to compensate for the loss of active metal ions in secondary battery systems (such as lithium-ion batteries, sodium-ion batteries, potassium-ion batteries, etc.). So far, a wide variety of sacrificial salts for secondary batteries have been reported, and common sacrificial salt additives include Li2S, Li3P, Li2O, Na2S, Na2CO3, Na2C2O4, K2O, KNO2, etc. These sacrificial salts have the advantages of being easy to obtain and having a high theoretical specific capacity. The main problems of sacrificial salts that have been studied more are poor ion and electronic conductivity and severe residual holes. Poor ion and electronic conductivity will cause the oxidative decomposition potential of sacrificial salts in the battery to be too high, exceeding the electrochemical window of the electrolyte, resulting in the sacrificial salts being unable to release active metal ions within the operating voltage range, and the improvement effect on battery performance is not obvious. In addition, after the sacrificial salts are decomposed, holes will be left on the electrode surface, resulting in the inability of the electrode material to be in close contact with the current collector, affecting the rate and cycle performance. For ease of understanding, the following is a specific introduction to pre-ionization from the perspective of sodium carbonate (Na2CO3), a sacrificial salt commonly used in sodium-ion batteries. Summary of the invention

[0003] The purpose of the present invention is to provide a method for preparing a sacrificial salt@C composite pre-ionized material, which has the characteristics of low material production cost, good mixing uniformity, excellent electrochemical performance and good electrolyte wettability.

[0004] The present invention can be implemented by the following technical solutions: The present invention discloses a method for preparing a sacrificial salt@C composite pre-ionized material, comprising the following steps: S1. Preparation of an alkali metal salt-organic carbon source mixed solution: adding a water-soluble organic carbon source to an alkali metal salt solution and stirring the mixture to obtain an alkali metal salt-organic carbon source mixed solution; S2. Preparation of a pre-ionized sacrificial salt complex precursor: spraying an alkali metal salt-organic carbon source mixed solution through spray drying to obtain a precursor; S3. Preparation of a composite pre-ionized sacrificial salt material for in-situ carbonization: calcining the prepared precursor at a high temperature in a protective atmosphere to obtain a composite pre-ionized sacrificial salt material for in-situ carbonization.

[0005] In the present invention, taking sodium carbonate as a sacrificial salt as an example, the theoretical specific capacity of Na2CO3 is 505.66 mAh / g. However, due to the large particle size of untreated commercial sodium carbonate particles and low electronic and ionic conductivity, when the cutoff voltage is 4.5 V (vs. Na / Na+ ), it only showed an actual capacity of 150 mAh / g, which is far lower than its theoretical specific capacity. Similarly, in lithium-ion batteries, pre-lithiation sacrificial salts such as Li2O have a high theoretical specific capacity of up to 1793.84 mAh / g, but due to poor conductivity and low electrochemical activity, their decomposition potential is higher than 4.7 V (vs. Li / Li + ), which exceeds the electrochemical stability window of conventional electrolytes for lithium-ion batteries and is difficult to play a role in practice. The high decomposition potential caused by the low electronic and ionic conductivity of sacrificial salts in secondary batteries has become a problem that hinders the practical application of sacrificial salts. Reducing the particle size and carbon coating are effective ways to reduce the decomposition voltage of sacrificial salts, which can make their decomposition voltage within the electrochemical window of the electrolyte and release almost all active metal ions in the first week. In addition, after the decomposition of the carbon-coated sacrificial salt, the residual carbon can partially fill the holes, solving the problem of the lack of close contact between the electrode material and the current collector after the decomposition of the sacrificial salt.

[0006] The modification method that combines spray drying and calcination can not only reduce the particle size of sacrificial salt particles, but also can carbonize in situ at high temperature to form a thin and uniform carbon coating layer, thereby improving the ionic and electronic conductivity of the sacrificial salt, improving the reaction kinetics of ion insertion and extraction, and solving the problems of insufficient conductivity and serious residual holes in traditional sacrificial salt materials.

[0007] Furthermore, in step S1, the molar ratio of the alkali metal salt to the organic carbon source is 2:1-12:1. In the present invention, the molar ratio of the alkali metal salt to the organic carbon source in step S1 will affect the effect of the present invention. When the molar ratio of the alkali metal salt to the organic carbon source is less than 2:1, the organic carbon source is excessive, and the carbon layer formed on the surface of the sacrificial salt is too thick. At this time, the conductivity of the sacrificial salt has reached the threshold value, and the excessive introduction of carbon will cause the capacity of the in-situ carbon-formed composite pre-ionized sacrificial salt to decrease, affecting the performance improvement; when the molar ratio of the alkali metal salt to the organic carbon source is greater than 12:1, the coating amount of the organic carbon source is too low, resulting in some sacrificial salt particles being exposed, and the conductivity performance is not significantly improved, which is not conducive to the sacrificial salt to exert its capacity and affects the actual pre-ionization effect.

[0008] Further, in step S2, the conditions for spray drying are: the inlet air temperature is 180-250 ° C, the outlet air temperature is 80-110 ° C, and the peristaltic pump speed is 8-15 rpm. In the present invention, the inlet air temperature, outlet air temperature and peristaltic pump speed of step S2 will affect the effect of the present invention. Specifically, when the inlet air temperature is lower than 180 ° C, the outlet air temperature is lower than 80 ° C, and the peristaltic pump speed is higher than 15 rpm, the water in the droplets cannot evaporate quickly, affecting the drying effect; when the inlet air temperature is higher than 250 ° C, the outlet air temperature is higher than 110 ° C, and the peristaltic pump speed is lower than 8 rpm, the monosaccharide organic carbon source will caramelize, causing the product to stick to the wall of the collection bottle, making it difficult to separate, affecting the product yield.

[0009] Further, in step S3, the conditions for high-temperature roasting are: the protective atmosphere is nitrogen and / or argon. The heating rate is 2-5 °C / min, the roasting temperature is 250-750 °C, and the holding time is greater than 5 h. In the present invention, the purpose of the roasting treatment in step S3 is to crack the organic carbon source into carbon and form a carbon coating on the surface of the sacrificial salt. The roasting temperature and holding time will affect the effect of the present invention. Specifically, if the roasting temperature is lower than 250 °C, the organic carbon source does not reach the temperature of pyrolysis into carbon, and a carbon coating cannot be formed on the surface of the sacrificial salt, which is not conducive to the improvement of the ionic and electronic conductivity of the sacrificial salt; if the roasting temperature is higher than 750 °C, the sacrificial salt will decompose and fail at high temperature, and the pre-ionization effect cannot be achieved; if the holding time is less than 5 h, the organic carbon source will not have enough carbonization time, and it cannot be fully pyrolyzed into carbon, resulting in a low actual carbonization amount, affecting the utilization rate of the organic carbon source.

[0010] Furthermore, in step S1, the alkali metal salt is one or more of lithium salt, sodium salt or potassium salt.

[0011] Furthermore, the alkali metal salt is one or more of Li2S, Li3P, Li2O, Na2S, Na2CO3, Na2C2O4, K2O, and KNO2.

[0012] Furthermore, the concentration of the alkali metal salt in the alkali metal salt-organic carbon source mixed solution is 0.25-1 mol / L. In the present invention, the concentration of the alkali metal salt in the alkali metal salt-organic carbon source mixed solution will affect the effect of the present invention. When the concentration of the alkali metal salt is less than 0.25 mol / L, the sacrificial salt content in the solution is too low, the product yield is low, and the energy consumption is high; when the concentration of the alkali metal salt is greater than 1 mol / L, the sacrificial salt content in the solution is too high, and a larger concentration will affect the morphology and size of the particles, causing the particle size to become larger and agglomerate.

[0013] Furthermore, in step S1, the organic carbon source is one or more of glucose, sucrose, soluble starch, citric acid monohydrate, cyclodextrin, polyethylene glycol, and water-soluble epoxy resin.

[0014] Furthermore, the concentration of the organic carbon source in the alkali metal salt-organic carbon source mixed solution is 0.02-0.17 mol / L.

[0015] The present invention provides a method for preparing a sacrificial salt@C composite pre-ionized material, which has the following beneficial effects: First, the production cost is low. The water-soluble organic carbon source is used as the raw material, which is low in cost. In addition, it can be pyrolyzed at a lower temperature during the roasting process to form a carbon coating layer on the surface of the alkali metal salt, which can greatly reduce the energy consumption in the production process. Second, the mixing uniformity is good. The alkali metal salt and the organic carbon source are first dissolved in water to form a uniform mixed solution, and then the solvent is removed by spray drying, so that the alkali metal salt and the organic carbon source are recrystallized to form uniform composite particles and sprayed out, which can effectively reduce the particle size and form a uniformly mixed precursor with the organic carbon source; Third, the electrochemical performance is excellent, which improves the problem of the traditional carbon coating that the capacity of the sacrificial salt complex decreases significantly due to the high carbon content. The in-situ carbonization method is used to form a thin and dense coating carbon layer. In the case of low carbon content, a stable carbon skeleton can still be constructed. While reducing the decomposition voltage of the sacrificial salt, the capacity of the sacrificial salt can be retained to the maximum extent, which is conducive to the effect of the pre-ionization reagent.

[0016] Fourth, the electrolyte has good wettability. The composite pre-ionized sacrificial salt prepared by spray drying-calcination is a micron-sized hollow sphere, which is conducive to the infiltration of the electrolyte, so that it can be decomposed to the maximum extent in the secondary battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 This is the charge-discharge curve of the first week of the Na2CO3@C composite sacrificial salt in situ carbonization in Example 1; Figure 2 The first week charge-discharge curve of NFPP with 8% Na2CO3@C composite sacrificial salt in Example 3; Figure 3 This is the first week charge and discharge curve of NFPP without sacrificial salt in comparative example 3. DETAILED DESCRIPTION

[0018] In order to enable those skilled in the art to better understand the technical solution of the present invention, the product of the present invention is further described in detail below in conjunction with embodiments.

[0019] The present invention discloses a method for preparing a sacrificial salt@C composite pre-ionized material, comprising the following steps: S1. Preparation of an alkali metal salt-organic carbon source mixed solution: adding a water-soluble organic carbon source to an alkali metal salt solution and stirring the mixture to obtain an alkali metal salt-organic carbon source mixed solution; S2. Preparation of a pre-ionized sacrificial salt complex precursor: spraying an alkali metal salt-organic carbon source mixed solution through spray drying to obtain a precursor; S3. Preparation of a composite pre-ionized sacrificial salt material for in-situ carbonization: calcining the prepared precursor at a high temperature in a protective atmosphere to obtain a composite pre-ionized sacrificial salt material for in-situ carbonization.

[0020] Furthermore, in step S1, the molar ratio of the alkali metal salt to the organic carbon source is 2:1-12:1.

[0021] Further, in step S2, the spray drying conditions are: the air inlet temperature is 180-250°C, the air outlet temperature is 80-110°C, and the peristaltic pump speed is 8-15 rpm.

[0022] Furthermore, in step S3, the high temperature calcination conditions are as follows: the protective atmosphere is nitrogen and / or argon, the heating rate is 2-5°C / min, the calcination temperature is 250-750°C, and the holding time is greater than 5 hours.

[0023] Furthermore, in step S1, the alkali metal salt is one or more of lithium salt, sodium salt or potassium salt.

[0024] Furthermore, the alkali metal salt is one or more of Li2S, Li3P, Li2O, Na2S, Na2CO3, Na2C2O4, K2O, and KNO2.

[0025] Furthermore, the concentration of the alkali metal salt in the alkali metal salt-organic carbon source mixed solution is 0.25-1 mol / L.

[0026] Furthermore, in step S1, the organic carbon source is one or more of glucose, sucrose, soluble starch, citric acid monohydrate, cyclodextrin, polyethylene glycol, and water-soluble epoxy resin.

[0027] Furthermore, the concentration of the organic carbon source in the alkali metal salt-organic carbon source mixed solution is 0.02-0.17 mol / L.

[0028] Example 1 The method for preparing the in-situ carbonization pre-ionized sacrificial salt composition for a secondary battery of this embodiment comprises the following steps: S1. Prepare an alkali metal salt-organic carbon source mixed solution: weigh 0.1 mol (10.5990 g) of sodium carbonate and stir it in 100 mL of deionized water for 5 min to obtain a sodium carbonate solution, then add 0.05 mol (9.9085 g) of glucose to the above solution and stir it for 5 min to obtain a sodium carbonate-glucose mixed solution.

[0029] S2. Preparing a pre-ionized sacrificial salt complex precursor: spraying a sodium carbonate-glucose mixed solution to obtain a precursor, wherein the inlet air temperature of the spray drying is 210°C, the outlet air temperature is 85°C, and the peristaltic pump speed is 12 rpm; S3, preparing a composite pre-ionized sacrificial salt material for in-situ carbonization; placing the prepared precursor in a tubular furnace, heating it to 550 °C at a rate of 2 °C / min in a nitrogen atmosphere, keeping it warm for 5 h, cooling it to room temperature and then taking it out to obtain a Na2CO3@C composite sacrificial salt material for in-situ carbonization; The electrochemical performance of the obtained material was tested according to the following method: Na2CO3@C composite sacrificial salt material, KB, and PVDF (4%) were mixed into a slurry in a mass ratio of 6:3:1, and the black slurry was coated on an aluminum foil using a 100 um four-sided preparation device, and then the aluminum foil was dried in a vacuum drying oven at 100 ℃ for 3 hours. The electrode film was punched into a disc with a diameter of 12 mm using a punching machine. Using metallic sodium as the counter electrode, 1M NaPF6EC / DEC / FEC (v:v:v=10:10:1) as the electrolyte, and a glass fiber diaphragm as the diaphragm, a CR2032 button cell was assembled in a glove box. The above button cell was subjected to constant current charge and discharge tests with a current density of 0.2 C (1 C=100 mAh / g) and a voltage range of 2-4.5 V (vs. Na / Na + The first week charging curve of the modified sodium carbonate is as follows Figure 1 As shown, the charging capacity in the first week reached 478.53 mAh / g.

[0030] Example 2 The method for preparing the in-situ carbonization pre-ionized sacrificial salt composition for a secondary battery of this embodiment comprises the following steps: S1. Prepare an alkali metal salt-organic carbon source mixed solution: weigh 0.15 mol (15.8985 g) of sodium carbonate and stir it in 150 mL of deionized water for 5 min to obtain a sodium carbonate solution, then add 0.0125 mol (4.2786 g) of sucrose to the above solution and stir it for 5 min to obtain a sodium carbonate-sucrose mixed solution.

[0031] S2. Preparing a pre-ionized sacrificial salt complex precursor: spraying a sodium carbonate-glucose mixed solution to obtain a precursor, wherein the inlet air temperature of the spray drying is 230°C, the outlet air temperature is 95°C, and the peristaltic pump speed is 10 rpm; S3. Preparation of composite pre-ionized sacrificial salt material with in-situ carbonization: placing the prepared precursor in a tube furnace, heating it to 750 °C at a rate of 2 °C / min in a nitrogen atmosphere, keeping it at that temperature for 5 h, cooling it to room temperature and then taking it out to obtain a composite sacrificial salt material with in-situ carbonization Na2CO3@C; Example 3 This embodiment provides a Na4Fe 2.91 The preparation process of the (PO4)2P2O7 half-cell includes the following steps: S1. Preparation of positive electrode sheet: The positive electrode active material Na4Fe 2.91 (PO4)2P2O7, conductive carbon AB, and binder PVDF (4%) were mixed in a mass ratio of 7:2:1, and then 8% by weight of Na2CO3@C composite sacrificial salt was added to the positive electrode active material. After mixing into a homogenous slurry, the black slurry was coated on an aluminum foil using a 100 um four-sided preparation device, and then the aluminum foil was dried in a vacuum drying oven at 100 °C for 3 hours. The electrode film was punched into a disc with a diameter of 12 mm using a punching machine to prepare Na4Fe2O3@C composite sacrificial salt-added Na4Fe2O3@C. 2.91 (PO4)2P2O7 electrode.

[0032] S2. Assemble half-cell: Use sodium metal as the counter electrode, 1M NaPF6 EC / DEC / FEC (v:v:v=10:10:1) as the electrolyte, and glass fiber diaphragm as the separator to assemble into CR2032 button cell in a glove box. Perform constant current charge and discharge test on the button cell with a current density of 0.1 C (1 C=100 mAh / g) and a voltage range of 2-4.5 V (vs. Na / Na + ). Its first week charge and discharge curve is as follows Figure 2 As shown, its first-week charging capacity reached 142.65 mAh / g, the discharge capacity was 100.68 mAh / g, and the first-week coulombic efficiency was 70.58%.

[0033] Comparative Example 3 This embodiment provides a Na4Fe 2.91 The preparation process of the (PO4)2P2O7 half-cell includes the following steps: S1. Preparation of positive electrode sheet: The positive electrode active material Na4Fe 2.91(PO4)2P2O7, conductive carbon AB, and binder PVDF (4%) were mixed into a slurry at a mass ratio of 7:2:1, and the black slurry was coated on an aluminum foil using a 100 um four-sided preparation device, and then the aluminum foil was dried in a vacuum oven at 100 °C for 3 hours. The electrode film was punched into a disc with a diameter of 12 mm using a punching machine to prepare Na4Fe 2.91 (PO4)2P2O7 electrode.

[0034] S2. Assemble half-cell: Use sodium metal as the counter electrode, 1M NaPF6EC / DEC / FEC (v:v:v=10:10:1) as the electrolyte, and glass fiber diaphragm as the separator to assemble into CR2032 button cell in a glove box. Perform constant current charge and discharge test on the button cell with a current density of 0.1 C (1 C=100 mAh / g) and a voltage range of 2-4.5 V (vs. Na / Na + ). Its first week charge and discharge curve is as follows Figure 3 As shown, its first-week charging capacity reached 103.66 mAh / g, its first-week discharge capacity reached 103.99 mAh / g, and its first-week coulombic efficiency was 100.32%.

[0035] Comparing Example 3 with Comparative Example 3, the charging capacity of Example 3 has increased by 38.99 mAh / g. The fundamental reason for the increase is that the pre-sodiumized sacrificial salt decomposes during the charging process, which increases the charging capacity of the positive electrode, while the irreversible decomposition of the sacrificial salt has almost no effect on the discharge capacity of the positive electrode material.

[0036] Example 4 The method for preparing the in-situ carbonization pre-ionized sacrificial salt composition for a secondary battery of this embodiment comprises the following steps: S1. Prepare an alkali metal salt-organic carbon source mixed solution: weigh 0.025 mol (3.3500 g) of sodium oxalate and stir it in 100 mL of deionized water for 5 min to obtain a sodium oxalate solution, then add 0.004 mol (1.3692 g) of sucrose to the above solution and stir it for 5 min to obtain a sodium oxalate-sucrose mixed solution.

[0037] S2. Preparing a pre-ionized sacrificial salt complex precursor: spraying a sodium oxalate-sucrose mixed solution to obtain a precursor, wherein the inlet air temperature of the spray drying is 210°C, the outlet air temperature is 85°C, and the peristaltic pump speed is 12 rpm; S3, preparing a composite pre-ionized sacrificial salt material for in-situ carbonization; placing the prepared precursor in a tubular furnace, heating it to 650 °C at a rate of 2 °C / min in a nitrogen atmosphere, keeping it warm for 8 h, cooling it to room temperature and then taking it out to obtain a Na2C2O4@C composite sacrificial salt material for in-situ carbonization; The electrochemical performance of the obtained material was tested according to the following method: Na2C2O4@C composite sacrificial salt material, AB, and PVDF (4%) were mixed into a slurry at a mass ratio of 7:2:1, and the black slurry was coated on an aluminum foil using a 100 um four-sided preparation device, and then the aluminum foil was dried in a vacuum drying oven at 100 ℃ for 3 hours. The electrode film was punched into a disc with a diameter of 12 mm using a punching machine. Using metallic sodium as the counter electrode, 1M NaPF6EC / DEC / FEC (v:v:v=10:10:1) as the electrolyte, and a glass fiber diaphragm as the diaphragm, a CR2032 button cell was assembled in a glove box. The above button cell was subjected to constant current charge and discharge tests with a current density of 0.2 C (1 C=100 mAh / g) and a voltage range of 2-4.5 V (vs. Na / Na + ). The first week charging capacity of the modified sodium oxalate is 329.53 mAh / g.

[0038] Example 5 The method for preparing the in-situ carbonization pre-ionized sacrificial salt composition for a secondary battery of this embodiment comprises the following steps: S1. Prepare an alkali metal salt-organic carbon source mixed solution: weigh 0.1 mol (4.5950 g) of lithium sulfide and stir it in 100 mL of deionized water for 5 min to obtain a lithium sulfide solution, then add 0.02 mol (3.2400 g) of soluble starch to the above solution and stir it for 5 min to obtain a lithium sulfide-soluble starch mixed solution.

[0039] S2. Preparing a pre-ionized sacrificial salt complex precursor: spraying a lithium sulfide-soluble starch mixed solution to obtain a precursor, wherein the inlet air temperature of the spray drying is 240°C, the outlet air temperature is 98°C, and the peristaltic pump speed is 8 rpm; S3, preparing a composite pre-ionized sacrificial salt material with in-situ carbonization; placing the prepared precursor in a tube furnace, heating it to 650 °C at a rate of 2 °C / min in an argon atmosphere, keeping it warm for 8 h, cooling it to room temperature and then taking it out to obtain a Li2S@C composite sacrificial salt material with in-situ carbonization; The electrochemical performance of the obtained material was tested according to the following method: Li2S@C composite sacrificial salt material, AB, and PVDF (4%) were mixed into a slurry at a mass ratio of 7:2:1, and the black slurry was coated on an aluminum foil using a 100 um four-sided preparation device, and then the aluminum foil was dried in a vacuum drying oven at 100 ℃ for 3 hours. The electrode film was punched into a disc with a diameter of 12 mm using a punching machine. Metal lithium was used as the counter electrode, 1M LiPF6EC / DEC / FEC (v:v:v=10:10:1) was used as the electrolyte, and the diaphragm was a glass fiber diaphragm. A CR2032 button cell was assembled in a glove box. The above button cell was subjected to constant current charge and discharge tests with a current density of 0.2 C (1 C=100 mAh / g) and a voltage range of 2.5-4.5 V (vs. Li / Li + ). The first week charging capacity of the modified lithium sulfide is 827.62 mAh / g.

[0040] Example 6 The method for preparing the in-situ carbonization pre-ionized sacrificial salt composition for a secondary battery of this embodiment comprises the following steps: S1. Prepare an alkali metal salt-organic carbon source mixed solution: weigh 0.1 mol (8.5104 g) of potassium nitrite and stir it in 100 mL of deionized water for 5 min to obtain a potassium nitrite solution, then add 0.01 mol (2.1014 g) of citric acid monohydrate to the above solution and stir it for 5 min to obtain a potassium nitrite-citric acid mixed solution.

[0041] S2. Preparing a pre-ionized sacrificial salt complex precursor: spraying a potassium nitrite-citric acid mixed solution to obtain a precursor, wherein the inlet air temperature of the spray drying is 180°C, the outlet air temperature is 80°C, and the peristaltic pump speed is 15 rpm; S3, preparing a composite pre-ionized sacrificial salt material with in-situ carbonization; placing the prepared precursor in a tube furnace, heating it to 250 °C at a rate of 2 °C / min in an argon atmosphere, keeping it warm for 7 h, cooling it to room temperature and then taking it out to obtain a KNO2@C composite sacrificial salt material with in-situ carbonization; The above embodiments are only specific embodiments of the present invention, and their descriptions are relatively specific and detailed, but they cannot be understood as limiting the scope of the present invention. It should be pointed out that for ordinary technicians in this field, several modifications and improvements can be made without departing from the concept of the present invention, and these obvious replacement forms all belong to the protection scope of the present invention.

Claims

1. A method for preparing a sacrificial salt@C composite pre-ionized material, characterized in that The following steps are involved: S1. Preparation of an alkali metal salt-organic carbon source mixed solution: adding a water-soluble organic carbon source to an alkali metal salt solution and stirring the mixture to obtain an alkali metal salt-organic carbon source mixed solution; S2. Preparation of a pre-ionized sacrificial salt complex precursor: spraying an alkali metal salt-organic carbon source mixed solution through spray drying to obtain a precursor; S3. Preparation of a composite pre-ionized sacrificial salt material for in-situ carbonization: calcining the prepared precursor at a high temperature in a protective atmosphere to obtain a composite pre-ionized sacrificial salt material for in-situ carbonization.

2. The method for preparing the sacrificial salt@C composite pre-ionized material according to claim 1, characterized in that: In step S1, the molar ratio of the alkali metal salt to the organic carbon source is 2:1-12:

1.

3. The method for preparing the sacrificial salt@C composite pre-ionized material according to claim 1, characterized in that: In step S2, the spray drying conditions are: the air inlet temperature is 180-250°C, the air outlet temperature is 80-110°C, and the peristaltic pump speed is 8-15 rpm.

4. The method for preparing the sacrificial salt@C composite pre-ionized material according to claim 1, characterized in that: In step S3, the high temperature calcination conditions are: the protective atmosphere is nitrogen and / or argon, the heating rate is 2-5°C / min, the calcination temperature is 250-750°C, and the holding time is greater than 5 hours.

5. The method for preparing the sacrificial salt@C composite pre-ionized material according to claim 1, characterized in that: In step S1, the alkali metal salt is one or more of lithium salt, sodium salt or potassium salt.

6. The method for preparing the sacrificial salt@C composite pre-ionized material according to claim 5, characterized in that: The alkali metal salt is one or more of Li2S, Li3P, Li2O, Na2S, Na2CO3, Na2C2O4, K2O, and KNO2.

7. The method for preparing the sacrificial salt@C composite pre-ionized material according to claim 6, characterized in that: The concentration of the alkali metal salt in the alkali metal salt-organic carbon source mixed solution is 0.25-1 mol / L.

8. The method for preparing the sacrificial salt@C composite pre-ionized material according to claim 1, characterized in that: In step S1, the organic carbon source is one or more of glucose, sucrose, soluble starch, citric acid monohydrate, cyclodextrin, polyethylene glycol, and water-soluble epoxy resin.

9. The method for preparing the sacrificial salt@C composite pre-ionized material according to claim 8, characterized in that: The concentration of the organic carbon source in the alkali metal salt-organic carbon source mixed solution is 0.02-0.17 mol / L.

Citation Information

Patent Citations

  • Preparation method of positive electrode material metal supplement of carbon-coated metal carbonate as well as product and application of positive electrode material metal supplement

    CN116902956A

  • Sacrificial positive electrode additive and preparation method and application thereof

    CN118522890A